Mise en jeu and Mise en geste - Eisenstein, Sergei; Eisenstein, Sergei (Book collections on Project MUSE., 2020)
In this essay the celebrated Soviet filmmaker and film theorist Sergei Eisenstein turns his attention not to cinematic montage, his signature concept, but to questions of staging and sequencing a film before its assembly in montage. Coining the expressions "mise en jeu" and "mise en geste", describing the work of actors and their gestures, he devised a novel theory of cinematic staging unlike any other and unlike. This is the only English translation of this rare view of an Eisenstein unfamiliar to us.